Sudden Sensorioneural Hearing Loss and Autoimmune Systemic Diseases - Rossini, Bruno Almeida Antunes; Penido, Norma de Oliveira; Munhoz, Mario Sergio Lei; Bogaz, Eduardo Amaro; Curi, Renata Souza (International Archives of Otorhinolaryngology, 2017)
Introduction Several authors have demonstrated the relationship between sudden sensorineural hearing loss (SNHL) and systemic autoimmune diseases (SAD). Immune-mediated SNHL can rarely present as unilateral sudden SNHL and manifests itself in the contralateral ear only after years. It presents clinical relevance for being one of the few SNHL that may be reversible given that early and appropriate treatment is applied.Objective The objective of this study is to describe the clinical presentations and audiological findings from patients with idiopathic sudden SNHL and SAD associated with a probable diagnosis of immune-mediated SNHL. Furthermore, we strive to estimate the prevalence of SAD in patients with sudden SNHL.Methods This is an observational retrospective cohort. We have selected and studied patients with SAD. Revision of available literature on scientific repositories.Results We evaluated 339 patients with sudden SNHL. Among them, 13 (3.83%) patients suffered from SAD. Three patients had bilateral involvement, a total of 16 ears. We evaluate and describe various clinical, epidemiological, and audiological aspects of this sample.Conclusion In our sample of patients with sudden SNHL, the prevalence of SAD was found relevant. The majority had tinnitus and dizziness concomitant hearing loss, unilateral involvement and had experienced profound hearing loss at the time of the installation. In spite of instituted treatment, most cases showed no improvement in audiometric thresholds. Apparently, patients with sudden SNHL and SAD have a more severe initial impairment, higher percentage of bilateral, lower response to treatment, and worse prognosis than patients with sudden SNHL of unknown etiology.
Keywords: hearing loss; sensorineural; hearing loss; sudden; autoimmune diseases; humans